Blood Urea Nitrogen/Albumin Ratio as A Predictor of Clinical Outcome in Sepsis - Ayuningtyas Caka Handayani; Tiene Rostini; Ratu Purwanti; Endang Budiati; Dian Utama Pratiwi Putri (GLOBAL HEALTH SCIENCE GROUP, 2025)
Sepsis is a life-threatening condition characterized by organ dysfunction resulting from a dysregulated immune response to infection. Sepsis is the leading cause of death from infection globally. Blood Urea Nitrogen (BUN) serves as a marker of kidney damage, and albumin is an indicator of fluid homeostasis. The BUN/albumin ratio can be used to predict mortality in infectious diseases,making it a widely studied and effective prognostic marker for mortality in sepsis patients. Analyzing the Blood Urea Nitrogen (BUN)/albumin ratio as a predictor of clinical outcome in sepsis patients. This retrospective cohort study used secondary data from laboratory results and electronic medical records of adult sepsis patients treated in intensive care units at RSUP Dr. Hasan Sadikin Bandung from January 2022 to December 2023. Patients were identified using ICD-10 code A41.9 and a Sequential Organ Failure Assessment (SOFA) score ≥2. Blood urea nitrogen and serum albumin levels were obtained from the first laboratory examination within 48 hours after ICU admission. A total of 139 patients who met the inclusion criteria were included. Statistical analysis was performed, with significance set at p<0.05. The subjects of this study included 139 sepsis patients, with a significant difference in the BUN/Albumin ratio between those who died and those who survived. The median BUN/albumin ratio was significantly higher in sepsis patients who died (16.58) compared to those who survived (9.16), p < 0.001. The analysis of the Receiver Operating Characteristic (ROC) curve showed an Area Under the Curve (AUC) of 0.814, indicating good predictive ability for mortality. The BUN/Albumin ratio with a cutoff of ≥10.1617 had a sensitivity and specificity of 73 and 71.8%, respectively. The Relative Risk in this study was 1.77, indicating that sepsis patients with a BUN/albumin ratio of ≥10.1617 had a 1.77 times higher risk of death compared to those with a BUN/albumin ratio of <10.1617. The BUN/albumin ratio is a significant predictor of mortality for determining clinical outcomes in sepsis patients. A higher BUN/albumin ratio is associated with increased mortality in sepsis patients, therefore the BUN/albumin ratio is useful as a prognostic marker of mortality in sepsis patients in clinical practice.